The features of social work of charitable funds with eldery - Садрицька, С. В.; Короп, А. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article is devoted to the problem of social work with the elderly, which requires the study and determination of the features of such work for various modern social services. The relevance of the topic of the article is due to the growing number of clients of social services among the elderly. Previous studies of the social needs of this category of the population predict worsening a number of problems due to the shortcomings of state social security. The solution to the problem, according to the authors of the article, is related to the activities of non-governmental organizations that can provide social services to the elderly. In particular, the article describes the experience of a charitable foundation that operates according to an atypical scheme of aid organization. Not through the provision of funds, but primarily through the implementation of their own projects with the support of other social services of various forms. The article discusses how the needs and characteristics of the elderly can be taken into account in practical social work with clients. The authors rely on the materials of their own research, which was conducted by case study from April to October 2019 on the experience of the Kharkiv Charitable Foundation «Social service of assistance». The article states that the main directions of social protection of the elderly in modern conditions should be not only to improve their difficult financial situation, provide a sufficient level of medical care but also to improve the psychological and emotional state of people. The results obtained by researchers can contribute to the dissemination of successful experience of social work with the elderly; scientific analysis of problematic issues and obstacles in the activities of the charity fund with the elderly; optimization of further work of funds and other social services in this direction. In addition, according to the authors, the hypothesis of indifferent attitude of society to the problems of the elderly needs to be studied scientifically, because this factor significantly hinders the implementation of social assistance to this group of clients by various social services, including charitable foundations.